The Origin of Prospect Theory, or Testing the Intuitive Statistician - Floris Heukelom (Tinbergen Institute, 2005)
The origin of prospect theory is the desire to test the intuitive statistician in the real world. The development of this theory by the cognitive psychologists Kahneman and Tversky can be traced to the former's work in cognitive psychophysics, in which deviations from average behavior are termed (statistical) errors; and the latter's work on decision theory, with its normative vs. descriptive framework. The combination of these two types of probabilistic psychology culminated in a new descriptive theory of human decision making in the real world, coined Heuristics and Biases. The 1979 Econometrica article applies this new descriptive theory to economists' EUT. It equates the intuitive statistician with the rational economic man and shows how it descriptively fails.
Keywords: B31; B41; D01; D81; 330; Kahneman and Tversky; Prospect Theory; Intuitive Statistician; Heuristics and Biases